Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

High-coverage paleo-genome research identifies a pathogenic mutation on EXT1 in a Qing-period Chinese individual with multiple osteochondromas - Bangyan Wang; Haodong Chen; Fanhao Xi; Haoquan Bao; Hetong Wen; Panxin Du; Chenshuang Sun; Jianxue Xiong; Baoshuai Zhang; Xin Chang; Yawei Zhou; Chuan-Chao Wang; et al. (Molecular Genetics and Genomics, 2026)

Characteristics and mechanism of karst groundwater cycle evolution under large-scale exploitation: a case study of the Yanxi karst groundwater system - Yawei Feng; Fengxin Kang; Fengfeng Shi; Xuesen Wang; Xianzhou Meng; Yifu Fu; Aijun Li; Hao Chen; Qingcheng He (Carbonates and Evaporites, 2026)

Synergistic enhancement of microalgal fatty acids via Batch Bayesian Optimization-driven combinatorial additive engineering - Yu Zhao; Yawei Wu; Guopeng Chen; Shi Guo; Fangzhong Wang; Lei Chen; Weiwen Zhang; Jie Chen (Bioresource Technology, 2026)

Aptamer/magnetic-MIP dual-recognition sandwich biosensor for rapid and recyclable determination of kanamycin in food - Tingting Wang; Fengjuan Zhao; Zhiguang Suo; Yong Liu; Yawei Huang; Min Wei (Analytica Chimica Acta, 2026)

Low-intensity electrical stimulation enhances phthalate ester biodegradation by activated sludge through real-time multi-scale regulation - Huabo Gong; Zhuo-Ning Xian; Jinwen Hu; Jinming Luo; Yawei Wang; Xiaowei Liu; Nanwen Zhu (Water Research, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Photocatalytic inhibition and mechanisms of adult Ulva prolifera by COF-supported CuS under visible light - Yingqi Zhang; Qingying Wei; Yun Tian; Yawei Zhang; Linqing Cui; Renjun Wang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2026)

Nitrogen sources and concentrations shape algal odor compounds: Key drivers of β-cyclocitral and β-ionone in water bodies of the lower Yangtze River - Sicheng Yin; Youyin Hu; Yawei Xing; Xianyun Wang; Erik Jeppesen; Liqing Wang; Wei Zhang (Journal of Environmental Sciences, 2026)

Robust water matrix tolerance for selective photocatalytic detoxification and decarboxylation of D-Glu and D-MeAsp in microcystin-LR via nanoconfinement-mediated active site regulation - Chengzhuo Yu; Jin Xu; Silong Wang; Li Xiong; Fanglan Geng; Yarui Wang; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2026)

Decoding flood hazard responses to reticular river network changes using interpretable machine learning - Shanheng Huang; Peng Wang; Zulin Hua; Yueyang Dong; Rongxu Chen; Yawei Hu; Shimin Tian (Journal of Hydrology, 2026)

Seasonal shifts in dissolved organic matter composition drive the formation of nitrogenous disinfection byproducts via a carbon-nitrogen coupling mechanism in source water - Tianyu Chen; Shiyang Yu; Qiurui Zhang; Jing Qian; Yonghong Bi; Anen He; Lingxiangyu Li; Nanwen Zhu; Jitao Lv; Zhigang Li; Yawei Wang; Guibin Jiang (Environmental Research, 2026)

Light-triggered molecular lever in a MOF@COF nanosheet for synergistic enhancement of heat and mass transfer in CO2 photothermal desorption - Jingyu Bao; Mingjie Zhou; Zuxue Bai; Yawei Xie; Xuehui Jia; Jiajun Zeng; Yujie Huang; Ruimeng Wang; Jianmin Chen; Zhaowei Jia; Liqin Zhou; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2026)

Urban–rural divergence of wintertime organic aerosol molecular fingerprints in PM2.5 revealed by FT–ICR MS - Shanshan Tang; Jintian Zhang; Yuansheng Wang; Jitao Lv; Lei Liu; Weijun Li; Yawei Wang (Atmospheric Environment, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

A functional lactic acid bacteria strain that naturally produces hydroxytyrosol and its impact on the antioxidant activity and post-acidification of fermented milk - Panpan Han; Yangliu Liu; Min Zhang; Yinglin Chen; Simiao Zhai; Zhixin Wang; Yawei Ning; Yingmin Jia (Food Bioscience, 2026)

Consistency and specificity of soil and microbial responses among crops to mulching practices in semi-arid rainfed agroecosystems in China - Yao Zhang; Yuwei Chai; Xichen Wang; Hongbo Cheng; Yawei Li; Jiantao Ma; Lei Chang; Shouxi Chai (European Journal of Agronomy, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Improved thermostability of Thermobifida fusca mannanase obtained by error-prone PCR mutagenesis - Yawei Wang; Qiang Xue; Guan Wang; Zhenggang Han; Jiangke Yang; Hairong Xiong (Biotechnology Letters, 2026)

Risk challenge in sustainable development: Volatility spillover networks and systemic importance of China’s new energy companies - Yawei Guo; Boxin Zhu; Youfen Lin; Ningli Wang (Environment, Development and Sustainability, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Cross-scale mechanisms and molecular–ecological thresholds of phthalate stress in the cucumber–soil system - Zhe Li; Lei Wang; DongDong Tuo; FuXin Huang; YaWei Shi; Ying Zhang (Journal of Hazardous Materials, 2026)

Revealing the protein dynamics of low-temperature Daqu during Daqu-making process by metaproteomics, enzyme activity assay, and ELISA - Shuai Zhao; Yunfei Xia; Xing Chen; Yan Chen; Xuezhuang He; Menqing Cui; Yuchen Gao; Lei Wang; Jing Lu; Yawei Shi (Food Bioscience, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

Sustainable lithium extraction from low-grade aqueous resources via reverse Li/Mg separation enabled by hydrated cation-π interaction - Huixiong Jiang; Xing Liu; Jin-Hang Liu; Xiudong Chen; Ruirui Wang; Yawei Wang; Changchao Zhan; Xiaohua Cao; Xiushen Ye; Guosheng Shi (Journal of Cleaner Production, 2026)

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

Accelerated peroxymonosulfate activation via internal electron migration within Co3O4/Bi2Fe4O9 for efficient phenol degradation - Bo Liu; Hangyu Shi; Yawei Wang; Rui Liu; Shuangshuang Zuo; Qianqian Nie; Lei Yang; Hesheng Yu (Journal of Environmental Sciences, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

Functional Lactiplantibacillus plantarum MT213 screened from traditional sourdough and its promising in-situ preservation in steamed bread - Danya Tong; Yajuan Zhang; Tianyi Zhang; Zhixin Wang; Shijie Wang; Xueming Xu; Yawei Ning (International Journal of Food Microbiology, 2026)

CLEC14A mediates trophoblast dysfunction in unexplained miscarriage by disrupting the cAMP/ERK signaling pathway - Jianing Wang; Yawei Shao; Linlin Zhou; Ruyue Ma; Shunli Dong; Ruiheng Zhao (Journal of Molecular Histology, 2026)

Netrin-1 protects against doxorubicin-induced cardiotoxicity by suppressing ferroptosis via the UNC5B-LKB1/CaMKKβ-AMPK-NRF2 axis - Wei Lu; Haibo Wu; Yanqing Wang; Yawei Duan; Peng Gao; Hongxiao Li; Rongpin Du (Molecular and Cellular Biochemistry, 2026)

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Soluble dietary fibers as structuring agents in gelatin gelation: Effects on phase behavior, network formation, water mobility, and colorant stability in low- and high-solid matrices - Ruican Wang; Yawei Chang; Richard W. Hartel; Ying Zhang; Shuo Wang (Food Hydrocolloids, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Injectable self-healing hydrogel for co-delivery of stem cells and growth factors in intervertebral disc regeneration - Zhiming Tu; Weichu Sun; Tao Yuan; Yuliang Dai; Xiaoya Ding; Yawei Li; Xiaocheng Wang; Bing Wang (Chemical Engineering Journal, 2026)

A chitosan-based composite scaffold as a bioactive strontium-delivery system mediating accelerated bone regeneration - Jiyang Zeng; Wei Li; Yawei Li; Zhiming Tu; Hong Ma; Yuliang Dai; Bing Wang; Hongbing Deng (Carbohydrate Polymers, 2026)

Transcriptome profiling of AP2/ERF family members and functional characterization of CaAP2/ERF99 in pepper defense against Phytophthora capsici - Jie Wang; Muhammad Azeem; Yawei Li; Beibei Gong; Xueqi Li; Li Liu; Guangqiang Wu; Moli Chu; Wei Cheng (Plant Science, 2026)

Microdroplet induced catalyst surface fields boost hydroxyl radical generation and its application - Ange Zhu; Jingkang Gao; Yunjun Mei; Mengxi Cao; Fengjie Chen; Bolei Chen; Yong Liang; Yawei Wang (Journal of Hazardous Materials, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Organic fractions in wastewater enabled simultaneous removal of NO3− and Cr(VI) under VUV185 irradiation - Yawei Xie; Shijie Wu; Xunfang Hu; Jinliang Wang; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Environmental Management, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Risk factors for antibiotic resistance and 30-day mortality among adult patients with acute leukemia and Escherichia coli bloodstream infection - Juan Wu; Wei Wang; Kaili Du; Zhongxian Liao; Yawei Shi; Munire Abudumaijiti; Jilai Liu; Jiadi Chen; Xinmiao Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Hysteretic behavior of reinforced ultra-high-performance concrete columns under combined axial and flexural loads - Qiwu Wang; Zhi Fang; Wenjie Zheng; Fei Peng; Yawei Fang; Jiaxing Chen; Hua Huang (Bulletin of Earthquake Engineering, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Cathodic periodate activation driven by photocatalytic fuel cell for ciprofloxacin degradation - Yawei Xie; Shijie Wu; Yaozu Jin; Xunfang Hu; Jinliang Wang; Miaomiao Ye; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Dual-pathway persulfate activation by mackinawite (FeS) for contaminant degradation: Overlooked role of Fe(IV) species and QSAR model - Bowen Yang; Zhihao Li; Yawei Liu; Qiang Ma; Dunqiu Wang; Longhui Zheng; Jiming Hao (Journal of Environmental Management, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

BRICS cooperation and ecological sustainability: Unveiling the roles of energy transition, technological innovation, and globalization - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang (Gondwana Research, 2026)

Untargeted metabolomics-based investigation of amino acid effects on antimicrobial peptides production in Paenibacillus ehimensis HD 8-3 fermentation - Chengling Feng; Jiapei Zhang; Yunfei Si; Zhen Zhao; Yawei Ning; Zhixin Wang (Food Bioscience, 2026)

Comparative assessment of physicochemical and functional properties of chestnut protein obtained by different extraction methods - Haoxin Cui; Yazhou Ji; Yawei Chang; Zhenting Yu; Fan Wei; Bowei Zhang; Yingshuang Lu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Novel enhanced network integrating transformations of DOM and microorganisms (ENITM) elucidates microbial-driven transformation pathways in estuarine sediments - Shiyang Yu; Jitao Lv; Xindong Ma; Lu Jiang; Qiurui Zhang; Tianyu Chen; Han Fang; Dong Cao; Lixia Zhao; Yawei Wang (Water Research, 2026)

Machine learning reveals molecular substructure drivers of organic contaminant translocation in crops - Haodong Lang; Yang Cui; Wen Liu; Shanshan Tang; Wei Gao; Chengyu Zhai; Jing Lu; Yawei Wang (Science of The Total Environment, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Spatial distribution and ecological risk assessment of pharmaceuticals and personal care products across China's coastal waters - Jia Shao; Tianyu Chen; Lu Jiang; Jitao Lv; Jingyu Zhang; Dan Wu; Fenfen Zhang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Phase-resolved multi-path drivers of PM2.5 evolution in eastern China under Clean Air Actions and carbon neutrality scenarios - Yasong Li; Lili Shen; Dandan Wei; Tijian Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie; Yanjin Wang (Journal of Hazardous Materials, 2026)

Anthropogenic filtering of detrital zircon and rutile signals in the Yangtze River: Implications for provenance reconstruction - Rujun Guo; Xianyan Wang; Xilin Sun; Wencke Wegner; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Urs Klötzli; Chang'an Li (Global and Planetary Change, 2026)

Cross-cultural consumer acceptance of sustainable protein-rich foods; legumes, plant-based meat analogues and hybrids, and cell-based foods - Isabella Tao Jakobsen; Marleen C. Onwezen; Yawei Wang; Fang Zhong; Derek Victor Byrne; Barbara Vad Andersen (Food Quality and Preference, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Molecular-scale mechanism of extracellular protein over-flocculation for sewage sludge dewatering by polyacrylamide - Minmin Liu; Jiesi Zhang; Yawei Zhao; Wei Wang; Huihui Zhang; Wenzheng Yu (Water Research, 2025)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

A multi-target QSAR model for simultaneously predicting the rate constants of reactions across multiple oxidation systems - Yawei Liu; Zhiquan Wang; Xiangyong Zheng; Min Zhao; Zhemin Shen (Journal of Hazardous Materials, 2025)

Efficient removal of nitrogen, phosphorus and antibiotics in freshwater aquaculture wastewater using a novel hybrid aeration biological filter - Dongyu Xia; Weina Dou; Yawei Tian; Lei Zhang; Cai Wang; Yong Wang; Jingyi Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xiang Mei (Journal of Environmental Management, 2025)

Occurrences and migration characteristics of photoinitiators in paper food packaging: Implication for human exposure - Chenge Qian; Lu Bai; Wen Wang; Yadan Luo; Juan Li; Yawei Wang (Journal of Environmental Sciences, 2025)

Involvement of two-component system CseB-C in differential regulation of rapamycin and elaiophylin biosynthesis in Streptomyces rapamycinicus - Yawei Zhao; Shangping Jin; Pan Wang; Yuan Wang; Na Liu; Aimei Liao; Zhe Sun; Yinhua Lu; Hailong Tian (Food Bioscience, 2025)

Unraveling the complex gelation dynamics of gelatin solutions mixed with various mono-, di-, or trisaccharides: A comparative study based on hydration properties - Ruican Wang; Yawei Chang; Yuanyifei Wang; Richard W. Hartel; Ying Zhang; Liye Zhu; Dancai Fan; Shuo Wang (Food Hydrocolloids, 2025)

Lactobacillus rhamnosus GG-derived extracellular vesicles improve cholestatic liver injury by regulating the gut microbiota and bile acid metabolism - Zhongyu Wang; Yubo Wang; Yawei Qiu; Andrea Del Pilar Abreo Medina; Yongwang Liu; Mengdie Shi; Jinyan Li; Yanyan Wang; Xianjiao Liu; Xingxiang Chen; Kehe Huang; Yunhuan Liu (Chemical Engineering Journal, 2025)

Microbial-mediated transformation shapes the molecular diversity of landfill leachate under anthropogenic and natural covariation - Qiurui Zhang; Jitao Lv; Shiyang Yu; Tianyu Chen; Yue Sun; Feifei Li; Lu Bai; Xianwei Wang; Xiaosong He; Yong Nie; Nanwen Zhu; Yawei Wang; et al. (Water Research, 2025)

Investigation on the effect of nanocellulose-enhanced short-chain fluorocarbon foam parameters on gasoline pool fire extinguishing performance - Yawei Lu; Jiahao Lai; Shaolin Liang; Xingyan Cao; Zhirong Wang; Yangqing Zhou (Process Safety and Environmental Protection, 2025)

Dual-action mechanism of Tamarix polyphenols in inhibiting IQ and MeIQ: Synergistic scavenging of free radicals and trapping of reactive carbonyls - Xiaopu Ren; Bing Xie; Mingyang Li; Shuai Kang; Wei Wang; Qianqian Yu; Yawei Zhang; Lujuan Xing (Food Chemistry, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

Environmental fate of POPs under climate change: Regulation of POPs distribution by soil organic matter and microbial communities during glacial retreat - Lu Jiang; Shiyang Yu; Jing Wu; Yan Gao; Xindong Ma; Jitao Lv; Wei Wang; Yihan Yu; Jia Shao; Yawei Wang; Hailin Wang; Guibin Jiang (Environmental Pollution, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Tuning electrode wettability to optimize nanobubble nucleation and reaction rates in water electrolysis - Zhenlei Wang; Yaxi Yu; Mengkai Qin; Hao Jiang; Zhenjiang Guo; Lu Bai; Limin Wang; Xiaochun Zhang; Xiangping Zhang; Yawei Liu (Chemical Engineering Journal, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

Numerical study on transient unloading fracture mechanism of deep hard rock under 3D stress path induced by drilling and blasting - Weiqi Wang; Yawei Zhang; Rui Kong; Qihu Wang; Yulong Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Population challenge, economy, energy decarbonization and information and communication technology: insights of ecological footprint and biocapacity in Belt and Road countries - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang; Zichuan Quan (Environment, Development and Sustainability, 2025)

A hybrid approach for optimizing soil greenhouse gas flux predictions: integrating machine learning outputs into hyperparameter-tuned regression trees - Mostafa RASTGOU; Shangkun LIU; Jin WANG; Yawei LI; Junzeng XU; Yong HE; Qianjing JIANG (Pedosphere, 2025)

Rapid cultivation regulation of Methyl tert-butyl ether degradation consortium: Effects of supplemental carbon source and mechanism - Wenhao Guo; Sunyin Wang; Jun Gu; Zixi Ming; Wei Wang; Xin Song; Yawei Qian; Manjun Zhan; Ran Yu (Journal of Environmental Chemical Engineering, 2025)

Effect of catalysts on the conversion of sulfur, nitrogen, and oxygen during catalytic/additives pyrolysis of oil sludge - Zhiguo Zheng; Zhipu Wang; Sikai Wu; Guangpu Li; Yawei Zhai; Lisong Zhou; Jun Yao (Journal of Environmental Chemical Engineering, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Deformation prediction modeling for levee structures based on environmental loads using SARIMAX and LSTM - Haiyang Li; Jing Wang; Shuguang Wu; Yawei Wang; Yehemin Gao; Guigen Nie (Advances in Space Research, 2025)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

Mediating role of whole epigenome DNA methylation signatures in the association between copper and SGA - Weiwei Wu; Mengru Wang; Shan Li; Bole Zhang; Weixuan Hu; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang (Journal of Trace Elements in Medicine and Biology, 2025)

Mechanism and application of phenyllactic acid on the control of yogurt post-acidification caused by Lactobacillus bulgaricus - Hongxin Zhou; Xuanxuan Pang; Panpan Han; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Research International, 2025)

Persistent O3 pollution over the North China Plain during the advancement of East Asian summer monsoon: Process analysis and interannual difference - Libo Gao; Tijian Wang; Xuejuan Ren; Yawei Qu; Hao Wu; Mengmeng Li; Min Xie (Atmospheric Research, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Methanol-driven advanced reduction of nitrate and 2,4,6-tribromophenol by UV-activated photolysis - Yawei Xie; Yue Wang; Shijie Wu; Hmuu Khet Nwe Zaw; Yaozu Jin; Shiyi Ni; Lyujun Chen; Hongyuan Liu (Process Safety and Environmental Protection, 2025)

Thermo-responsive hydrogel evaporator via In-Situ chromogenic strategy for high-efficiency solar desalination with robust salt resistance - Ju Lv; Lang Pan; Yawei Zhu; Xinyue Zhang; Liujin Yang; Xiudie Wang; Xueqiong Yin (Chemical Engineering Journal, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Gram-scale synthesis of unsupported Pt-rare earth nanosponge for enhanced stability in proton exchange membrane fuel cells - Chenhao Li; Hao Wang; Fangren Qian; Yawei Li; Qinqin Sang; Qingjun Chen; Jialiang Liao; Yihan Zhu; Yanrong Liu; Suojiang Zhang (Chemical Engineering Journal, 2025)

Quaternary ammonium COF-based proton exchange membranes for enhanced electrochemical hydrogen compression - Xiao Pang; Ziwen Liu; Shuting Xu; Kexin Lv; Benbing Shi; Xu Dong; Na Xing; Zhong Gao; Shiyi Zhu; Leilang Zhang; Zengguang Yao; Lijuan Cheng; et al. (Chemical Engineering Journal, 2025)

Killing two birds with one stone strategy inspired advanced batteries with superior thermal safety: A comprehensive evaluation - Junling Wang; Konghao Yu; Peng Xiao; Li Li; Chunlin Wang; Zhirong Wang; Dongliang Guo; Yuen Kwok Kit Richard; Yawei Lu (Chemical Engineering Journal, 2025)

Experimental study on the failure mechanism of interbedded anti-dip rock slope induced by underground mining - Nanyun Wang; Zuliang Zhong; Yawei Xu; Xinrong Liu; Kaixin Zhu (Journal of Mountain Science, 2025)

Sustainable Ca(OH)2 deacidifiers derived from waste eggshells for free fatty acids removal: characterization, performance and thermodynamics - Yawei Wang; Chao He; Gang Li; Xinxin Liu; Liang Liu; Youzhou Jiao (Environment, Development and Sustainability, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Removal of adsorbable organic halogens generated during advanced oxidation processes using UV/sulfite - Yawei Xie; Yue Wang; Mingdi Yang; Shijie Wu; Yaozu Jin; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2025)

Anti-inflammatory effect of food bioactives in inflammatory bowel disease: Role of the gut microbiome - Yawei Zhang; Lufan Zhang; Yang Dong; Yunwei Yang; Mengxing Li; Qian Chen; Dan Wang; Yuzheng Wu; Tao Wang (Food Bioscience, 2025)

The impact of indoor air quality on work performance in urban office spaces: A machine learning approach - Xinyi Huang; Xiaohong Zheng; Yawei Xu; Jiale Zhai; Dengyun Wang; Hua Qian (Building and Environment, 2025)

Distribution, removal and potential factors affecting antibiotics occurrence in leachate from municipal solid waste incineration plants in China - Xuan Rui; Huabo Gong; Jinwen Hu; Haiping Yuan; Yawei Wang; Lixia Yang; Nanwen Zhu (Water Research, 2025)

Investigation on the inhibition mechanism of thermal runaway propagation in high-rate cycling lithium-ion pouch cells - Yajun Huang; Xiongqi Shen; Yinquan Zhao; Junling Wang; Yang Cao; Wei Bai; Yu Fan; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2025)

Synergy of bismuth and tungsten in Bi2WO6 for PMS activation to enhance degradation of ammonium dibutyl dithiophosphate in flotation wastewater - Mingwei Shen; Teng Wang; Yawei Wang; Zhiyuan Li; Jiayou Liu; Ke Jin; Hesheng Yu (Journal of Water Process Engineering, 2025)

Impact of aerosol-radiation interaction and heterogeneous chemistry on the winter decreasing PM2.5 and increasing O3 in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Journal of Environmental Sciences, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

The Preconditioning with Sevoflurane Alleviates Hypoxia-Reoxygenation-Induced Myocardial Cell Injury by Regulating the lncRNA LINC00265/miR-370-3p Axis - Yangge Shao; Qiang Gu; Yawei Yuan; Long Wang; Taowei Yu (Cardiovascular Toxicology, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Sucrose laurate and nisin synergistically inhibit Bacillus subtilis by multiple antibacterial targets and play promising application potential in bread preservation - Danya Tong; Panpan Han; Mingrui Li; Zhixin Wang; Zhen Zhao; Yingmin Jia; Yawei Ning (Food Chemistry, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Stability analysis of karst anti dip rock slope induced by underground coal mining - A case study of Jiguanling landslide, China - Zuliang Zhong; Erwei Liang; Nanyun Wang; Yawei Xu (Journal of Mountain Science, 2025)

Eco-friendly design of active montmorillonite nanofillers for reinforcing the anti-corrosion property of epoxy coating - Xianliang Li; Yawei Shao; Yanqiu Wang; Junyi Wang (Applied Clay Science, 2025)

Research on multi-objective control algorithm for micro-nano satellite formation based on array signal detection - Jiao Wang; Boao Zhu; Chengshang Li; Chong Sun; Yawei Wan (Advances in Space Research, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Accurate prediction of pollution and health risks of iodinated X-ray contrast media in Taihu Lake with machine learning and revealing key environmental factors - Xinying Cheng; Yuteng Zhang; Sirui Yan; Qingsong Ji; Xiangcheng Kong; Huiming Li; Shiyin Li; Shaogui Yang; Zhigang Li; Yawei Wang; Limin Zhang; Huan He (Water Research, 2025)

Nonlinear dynamic analysis of a 3D land-fixed oscillating water column wave energy converter - Dezhi Ning; Yawei Sun; Rongquan Wang; Peiwen Cong (Ocean Engineering, 2025)

Revealing global supply risk of critical minerals essential for low-carbon energy technologies - Xinran Xing; Yawei Huang; Yao Wang; Heming Wang; Peng Wang; Tao Dai; Gang Liu; Asaf Tzachor (Journal of Cleaner Production, 2025)

Study on the deterioration of bond-slip performance of rockbolt grouted structures under corrosion - Shuisheng Yu; Shucan Lu; Yawei Wang; Hongsen Zhang; Fuzhou Qi (Computers and Geotechnics, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Recent advances in groundwater pollution research using machine learning from 2000 to 2023: A bibliometric analysis - Xuan Li; Guohua Liang; Bin He; Yawei Ning; Yuesuo Yang; Lei Wang; Guoli Wang (Environmental Research, 2025)

The individualized optimal pillow height and neck support design for side sleepers - Shan Tian; Chenghong Yao; Yawei Wang; Xuepeng Cao; Yike Sun; Lizhen Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2025)

Ensuring high integrity of GNSS precise orbit and clock products based on performance-assured sliding-window innovation test - Yingchao Xiao; Xingqun Zhan; Shizhuang Wang; Yawei Zhai (Advances in Space Research, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

A comprehensive screening method of oxidation systems based on reaction rate constant (k value) and emergy (Em value) - Yawei Liu; Zhiquan Wang; Zhiwen Cheng; Yuanyang Ren; Yujia Tan; Tao Yuan; Zhemin Shen (Science of The Total Environment, 2025)

Assessing the environmental impacts associated with China's battery minerals and technologies - Yawei Huang; Heming Wang; Asaf Tzachor (Resources, Conservation and Recycling, 2025)

A hybrid TCN-BiLSTM short-term load forecasting model for ship electric propulsion systems combined with multi-step feature processing - Shuo Pang; Liang Zou; Li Zhang; Hui Wang; Yawei Wang; Xingdou Liu; Jundao Jiang (Ocean Engineering, 2025)

Unveiling the impact of aging on environmental sustainability in China: New insights from the Fourier ARDL approach - Zichuan Quan; Xi Xu; Jikun Jiang; Weihao Wang; Yawei Xue; Ling Jiang (Journal of Environmental Management, 2025)

Synchronised removal of nitrogen and sulphate from rubber industrial wastewater by coupling of Sulfammox and sulphide-driven autotrophic denitrification in anaerobic membrane bioreactor - Ishanka Wimalaweera; Fumin Zuo; Qihe Tang; Qianwen Sui; Shameen Jinadasa; Sujithra Weragoda; Tharindu Ritigala; Rohan Weerasooriya; Yawei Wang; Hui Zhong; Madhubhashini Makehelwala; Yuansong Wei (Bioresource Technology, 2025)

Effects of traffic noise on the psychophysiological responses of college students: An EEG study - Nan Zhang; Chao Liu; Menglin Zhang; Yawei Guan; Wenhua Wang; Zihao Liu; Weijun Gao (Building and Environment, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Hedge three-dimensional reconstruction and motion control technology for trimming robot - Jin Gu; Bin Zhang; Yu Wang; Yawei Zhang (Computers and Electronics in Agriculture, 2024)

Insight into the keystones of Chinese broad bean paste fermentation: Brewing techniques, chemosensory characteristics, and microbial community - Shuai Zhao; Chang Hao; Chengtuo Niu; Jing Lu; Lei Wang; Yawei Shi; Qi Li (Trends in Food Science & Technology, 2024)

Hydrological interactions between surface water and groundwater in ancient manmade village tank cascade systems (VTCSs) in the dry zone of Sri Lanka - Suresh Indika; Dazhou Hu; Yuansong Wei; Isuru Yapabandara; Samadhi Athauda; Ashen Randika; Sangeeth Prasad; Titus Cooray; Madhubhashini Makehelwala; Hui Zhong; Yawei Wang; K.B.S.N. Jinadasa; et al. (Science of The Total Environment, 2024)

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

Molecular designing of potential environmentally friendly PFAS based on deep learning and generative models - Ying Yang; Zeguo Yang; Xudi Pang; Huiming Cao; Yuzhen Sun; Ling Wang; Zhen Zhou; Pu Wang; Yong Liang; Yawei Wang (Science of The Total Environment, 2024)

The effect of anthropogenic activities on the behavior of novel brominated flame retardants in surface soil of Northern China urbanized zone - Ziyan Liu; Yaqi Zhang; Feifei Li; Huifang Zhong; Runzeng Liu; Qiu Zhang; Rongguang Shi; Yingjun Wang; Yawei Wang (Science of The Total Environment, 2024)

Effects of saccharide type and extended heating on the Maillard reaction and physicochemical properties of high-solid gelatin gels - Ruican Wang; Xinyu Zhai; Richard W. Hartel; Yawei Chang; Wenwen Pang; Wen Han; Huan Lv; Shuo Wang (Food Chemistry, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

Optimal conditions for cryopreservation by vitrification of largemouth bass (Micropterus salmoides) embryos - Meng Zhang; Xiao Ma; Yuqing Han; Zerui Wang; Zhilin Jia; Dongcai Chen; Zhigang Qiao; Xiaotian Gao; Chunlong Zhao; Yawei Shen (Animal Reproduction Science, 2024)

Drivers of change behind the spatial distribution and fate of typical trace organic pollutants in fresh waste leachate across China - Huabo Gong; Jinwen Hu; Xuan Rui; Yawei Wang; Nanwen Zhu (Water Research, 2024)

Characteristics of disinfection byproducts from dissolved organic matter during chlor(am)ination of source water in Tibetan Plateau, China - Ruiqing Chen; Tianyu Chen; Yukun Zhou; Linfeng Li; Lingxiangyu Li; Nali Zhu; Zhigang Li; Yawei Wang; Guibin Jiang (Science of The Total Environment, 2024)

Deciphering the seasonal dynamics of multifaceted aerosol-ozone interplay: Implications for air quality management in Eastern China - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Jiachen Fan; Min Shao; Min Xie (Science of The Total Environment, 2024)

Short time-series expression transcriptome data reveal the gene expression patterns and potential biomarkers of blood infection with LPS and poly (I:C) in Mandarin fish (Siniperca chuatsi) - Yawei Shen; Rahma Sakina Said Aly; Tiantian Chen; Hewei Jiang; Yufei Liu; Yongxiang Wang; Xiaowu Chen (Fish & Shellfish Immunology, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Effects of inorganic sodium on the soot generation of coal particle: Insights with PLIF and DFT calculation - Yawei Song; Sheng Su; Zheng Zhao; Jingyan Wang; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2024)

Inactivation mechanism of phenyllactic acid against Bacillus cereus spores and its application in milk beverage - Dongchun Zhang; Danya Tong; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Chemistry, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

The joint impact of PM2.5, O3, and CO2 on the East Asian Summer Monsoon in 2013 and 2018 due to contrasting emission reduction - Danyang Ma; Tijian Wang; Hao Wu; Yawei Qu; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Natalya Andreeva Kilifarska-Nedialkova (Atmospheric Environment, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Antifungal mechanism of Lactiplantibacillus plantarum P10 against Aspergillus niger and its in-situ biopreservative application in Chinese steamed bread - Mengge Ma; Ao Li; Jin Feng; Zhixin Wang; Yingmin Jia; Xinying Ma; Yawei Ning (Food Chemistry, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

High throughput identification of carbonyl compounds in natural organic matter by directional derivatization combined with ultra-high resolution mass spectrometry - Shiyang Yu; Shanshan Tang; Jitao Lv; Feifei Li; Zichun Huang; Lixia Zhao; Dong Cao; Yawei Wang (Water Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Assessment major NOx sources to nitrate of TSP around the Danjiangkou reservoir using isotopes and a Bayesian isotope mixing model - Chunyan Xiao; Yimeng Sun; Tongqian Zhao; Guizhen Wang; Pengbo Li; Yawei Zhao; Feihong Chen (Atmospheric Pollution Research, 2024)

A real-time accuracy prediction model on time-relative positioning method considering the correlation of position increment errors - Xuan Zou; Zhiyuan Li; Weiming Tang; Yawei Wang; Yangyang Li; Siyu Zhang; Yongfeng Zhang (GPS Solutions, 2024)

The application of chitosan quaternary ammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering - Minmin Liu; Sajid Rashid; Wei Wang; Huihui Zhang; Yawei Zhao; Xingmin Fu; Zhaoyang Su; Nigel Graham; Wenzheng Yu (Water Research, 2024)

Long‒term trends in surface thermal environment and its potential drivers along the urban development gradients in rapidly urbanizing regions of China - Chengyu Zhao; Hongkai Zhu; Shuyi Zhang; Ziwen Jin; Yiwen Zhang; Yawei Wang; Yadie Shi; Jianhui Jiang; Xiaoyong Chen; Min Liu (Sustainable Cities and Society, 2024)

Experimental investigation for the effect of bust pressure on hydrogen explosion venting - Yawei Lu; Rujia Fan; Zhirong Wang; Xingyan Cao; Yongjun Li; Chendi Lin; Zhuohua Yang (Fuel, 2024)

An impact of l-histidine on the phosphorylation and stability of pyruvate kinase at low NaCl level - He Wanhong; Peng Yingbo; Wang Wenqi; Jamali Muneer Ahmed; Teng Shuang; Peng Zengqi; Zhang Yawei (Food Chemistry, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Characteristics of advanced anaerobic digestion sludge-based biochar and its application for sewage sludge conditioning - Qian Chen; Xingmin Fu; Jiawei Wang; Yawei Zhao; Wei Wang; Abdul Ghaffar Memon; Huihui Zhang; Yang Wen (Bioresource Technology, 2024)

Exploring the role of aerosol-ozone interactions on O3 surge and PM2.5 decline during the clean air action period in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'’geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Atmospheric Research, 2024)

Effects of Dietary Valine Chelated Zinc Supplementation on Growth Performance, Antioxidant Capacity, Immunity, and Intestine Health in Weaned Piglets - Tuan Zhang; Nan Zhang; Shuyu Peng; Yawei Zhang; Huakai Wang; Shiyu Huang; Min Zhu; Yongxi Ma (Biological Trace Element Research, 2024)
This study was conducted to investigate the effects of dietary valine chelated zinc (ZnVal) supplementation on growth performance, antioxidant capacity, immunity, and intestine health in weaned piglets. A total of 240 healthy 35-day-old weaned piglets (Duroc × Landrace × Yorkshire, average weight 10.70 ± 0.14 kg) were randomly divided into five groups with six replicate pens and eight piglets per pen. Dietary treatments were a corn–soybean meal basal diet supplemented with 0, 25, 50, 75, and 100 mg/kg ZnVal, respectively. The experiment lasted for 28 days. Results showed that average daily gain (ADG) was increased ( P < 0.05) by ZnVal with 75–100 mg/kg supplementation on days 15–28 and with 50–100 mg/kg supplementation on days 1–28. Supplementation of 25–100 mg/kg ZnVal reduced ( P < 0.01) the diarrhea rate of weaned piglets on days 1 to 14 and 1 to 28. Dietary supplementation with 25–100 mg/kg ZnVal increased ( P < 0.05) copper/zinc-superoxide dismutase (Cu/Zn-SOD) and decreased malonaldehyde (MDA) activities in the serum on day 14 and 28. Supplementation of 25–100 mg/kg ZnVal increased ( P < 0.05) glutathione peroxidase (GSH-Px) activity in serum on day 14. Additionally, the supplementation of 75 mg/kg ZnVal significantly increased the activity of superoxide dismutase (SOD) and Cu/Zn-SOD in the liver ( P < 0.05). Furthermore, the supplementation of 25–100 mg/kg ZnVal significantly increased the total antioxidant capacity (T-AOC) in the liver ( P < 0.05). Higher ( P < 0.05) concentrations of IgG in the serum were measured from piglets supplemented with 75–100 mg/kg ZnVal on day 14 and dietary supplementation with 25–100 mg/kg ZnVal increased the level of immunoglobulin G (IgG) in serum on day 28 ( P < 0.05). In addition, higher ( P < 0.05) concentrations of immunoglobulin A (IgA) in the duodenum and ileum were measured from piglets supplemented with 75 mg/kg ZnVal and the supplementation of 25–100 mg/kg ZnVal also showed a higher ( P < 0.05) concentration of immunoglobulin G (IgG) in duodenum. Supplementation of 50–100 mg/kg ZnVal increased the villus height and villus height/crypt depth of jejunum ( P < 0.05). Moreover, dietary supplementation with 75–100 mg/kg ZnVal showed a higher ( P < 0.05) concentration of zinc in the liver and supplementation of 50–100 mg/kg ZnVal increased ( P < 0.05) the concentration of zinc in the heart, spleen, and kidney. In conclusion, the present research showed that supplementation of ZnVal improves growth performance by increasing antioxidant capacity and immunity and regulating intestinal morphology and the optimal inclusion level of ZnVal was 65~80 mg/kg.

Experimental study on the progressive collapse mechanism of excavations retained by tied-back retaining systems - Gang Zheng; Ruozhan Wang; Xuesong Cheng; Qiang Zhou; Yawei Lei; Shixiong Wu; Fan Yi (Tunnelling and Underground Space Technology, 2024)

Hydrothermal liquefaction of pig carcasses to biofuel: A techno-economic analysis - Youzhou Jiao; Chao Chang; Gaojie Xu; Chao He; Xinxin Liu; Gang Li; Yawei Wang; Xiaohui Pan; Guizhuan Xu; Qibin Li; Liang Liu (Process Safety and Environmental Protection, 2024)

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Degradation metabolic pathway of low-rank coal using single hydrolytic bacteria - Daping Xia; Yunxia Niu; Jixian Tian; Xianbo Su; Guoqin Wei; Kuo Jian; Zhenzhi Wang; Yawei Zhang; Weizhong Zhao (Fuel, 2024)

Photo-Enhanced Lead-Free Antimony-Based perovskite triboelectric nanogenerator for Dual-Mode detector - Ling Ding; Zhan Wei; Na Sun; Yawei Cai; Yanhong Zhou; Kan Fang; Guigen Wang (Chemical Engineering Journal, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Pollution levels and probability risk assessment of potential toxic elements in soil of Pb–Zn smelting areas - Mingyue Li; Jinyang Zhou; Zhiwen Cheng; Yuanyang Ren; Yawei Liu; Linling Wang; Liu Cao; Zhemin Shen (Environmental Geochemistry and Health, 2024)

Enhanced fluid mixing using a novel multi-stage static pipeline mixer: Numerical simulation and mechanism analysis - Jiaheng Zhao; Xing Li; Zedong Lu; Wenjun Chi; Zhibin Wang; Yawei Chen (Journal of Water Process Engineering, 2024)

Biological effects of perfluoroalkyl substances on running water ecosystems: A case study in Beiluo River, China - Xi Li; Qiang Wang; Qi Li; Yawei Wang; Yulu Tian; Anen He; Yan Chen; Shaocheng Si (Journal of Hazardous Materials, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Improved yield by optimizing carbon, nitrogen metabolism and hormone balance in apical kernels under low nitrogen conditions using the low nitrogen–tolerant maize variety - Qinlin Liu; Xinglong Wang; Yawei Wu; Tianqiong Lan; Fan Liu; Gui Wei; Chengcheng Lv; Fanlei Kong; Jichao Yuan (Field Crops Research, 2024)

Surviving punishment by body reduction in a hierarchical society: A bioarcheological study of two punitive amputation cases in Eastern Zhou Dynasty (771–256 BCE) with references to the penal and medical systems of ancient China - Yawei Zhou; Yanmei Liu; Fei Yan; Qian Wang (Archaeological and Anthropological Sciences, 2024)

Proteome and gut microbiota analysis of Chinese mitten crab (Eriocheir sinensis) in response to Hepatospora eriocheir infection - Yawei Cao; Leiting Zhang; Yue Yang; Jiaying Li; Xiaoqi Luan; Xiaoli Xia; Wei Gu; Jie Du; Keran Bi; Li Wang; Qingguo Meng (Aquaculture, 2024)

Characterization of short-, medium-, and long-chain chlorinated paraffins in Tibetan butter and implications for local human exposure - Lu Jiang; Xindong Ma; Yuzhen Ciren; Jing Wu; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2024)

Hollow core-shell B-g-C3N4-x@Bi2S3/In2S3 dual S-scheme heterojunction photothermal nanoreactor: Boosting photothermal catalytic activity in confined space - Yawei Xiao; Haoyu Li; Bao Yao; Yude Wang (Chemical Engineering Journal, 2024)

Comprehensive visual information acquisition for tomato picking robot based on multitask convolutional neural network - Xiaoqiang Du; Zhichao Meng; Zenghong Ma; Lijun Zhao; Wenwu Lu; Hongchao Cheng; Yawei Wang (Biosystems Engineering, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

Migration mechanism and risk assessment of per- and polyfluoroalkyl substances in the Ya'Er Lake oxidation pond area, China - Chang Li; Huifang Zhong; Jing Wu; Lingyi Meng; Yingjun Wang; Chunyang Liao; Yawei Wang; Yujian He (Journal of Environmental Sciences, 2024)

Research on the inhibition characteristics of ultrafine water mist on gas/dust two-phase mixture explosions - Xingyan Cao; Chaodong Wang; Yue Wang; Zhirong Wang; Haoyue Wei; Yawei Lu (Fuel, 2024)

A dual-emitting fluoroprobe fabricated by aloe leaf-based N-doped carbon quantum dots and copper nanoclusters for nitenpyram detection in waters by virtue of inner filter effect and static quenching principles - Junxia Wang; Yueying Sun; Panpan Wang; Zhengpeng Sun; Yawei Wang; Ming Gao; Huili Wang; Xuedong Wang (Analytica Chimica Acta, 2024)

A critical review on the bioaccumulation, transportation, and elimination of per- and polyfluoroalkyl substances in human beings - Yao Lu; Ruining Guan; Nali Zhu; Jinghua Hao; Hanyong Peng; Anen He; Chunyan Zhao; Yawei Wang; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2024)

New insights into Co3O4-carbon nanotube membrane for enhanced water purification: Regulated peroxymonosulfate activation mechanism via nanoconfinement - Huanran Ma; Guoqing Feng; Xiao Zhang; Chengwen Song; Ruisong Xu; Yawei Shi; Pengcheng Wang; Zhouhang Xu; Guanlong Wang; Xinfei Fan; Zonglin Pan (Chemosphere, 2024)

Maximizing the carbon sink function of paddy systems in China with machine learning - Jin Wang; Qingguan Wu; Yong He; Yawei Li; Junzeng Xu; Qianjing Jiang (Science of The Total Environment, 2024)

A technical evaluation on the mathematical attitudes and fitting accuracy of soil moisture retention curve models - Mostafa Rastgou; Yong He; Jin Wang; Hossein Bayat; Meihong Shao; Yawei Li; Qianjing Jiang (Computers and Electronics in Agriculture, 2023)

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

Mesopore-enhanced graphene electrodes with modified hydrophilicity for ultrahigh capacitive deionization - Ting Yang; Hongmei Zhang; Linpei Guo; Jing Wang; Zhiyuan Guo; Yawei Du; Jie Liu; Yingying Zhao; Panpan Zhang; Zhi-Yong Ji (Desalination, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Bioconcentration of polycyclic aromatic hydrocarbons in different tissues of zebrafish (Danio rerio) investigated with PBTK model - Yawei Zhai; Haotian Wang; Xiaohan Lin; Xinghui Xia (Environmental Science and Pollution Research, 2023)

Quantitative generation of ROS and their effective photocatalytic antibacterial activity of high-intensity universal P25 network films: The role of ROS - Jin Xu; Chengzhuo Yu; Silong Wang; Li Xiong; Fanglan Geng; Jitao Lv; Lixia Zhao; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Charge-tuning mediated rapid kinetics of zinc ions in aqueous Zn-ion battery - Yawei Xiao; Jie Ren; Mengyao Li; Kai Xiao; Yude Wang (Chemical Engineering Journal, 2023)

Coating TiO2 with MIL-101(Fe) to decarboxylate D-Glu and D-MeAsp of microcystin-LR from HA-rich water: Diminishing the inhibitory effect of humic acids - Yarui Wang; Chengzhuo Yu; Sen Wang; Jin Xu; Fanglan Geng; Silong Wang; Jitao Lv; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Experimental investigation on a novel and hyper-efficient oscillating water column wave energy converter coupled with a parabolic breakwater - Robert Mayon; Dezhi Ning; Yawei Sun; Zhenyu Ding; Rongquan Wang; Yu Zhou (Coastal Engineering, 2023)

Study on the assimilation of the sulphate reaction rates based on WRF-Chem/DART - Congwu Huang; Chaoqun Ma; Tijian Wang; Yawei Qu; Mengmeng Li; Shu Li; Bingliang Zhuang; Min Xie (Science China Earth Sciences, 2023)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Investigation with ESI FT-ICR MS on sorbent selectivity and comprehensive molecular composition of landfill leachate dissolved organic matter - Qiurui Zhang; Jitao Lv; Anen He; Dong Cao; Xiaosong He; Lixia Zhao; Yawei Wang; Guibin Jiang (Water Research, 2023)

Identification of lower brominated bisphenol A analogs as the photooxidation products of tetrabromobisphenol A bis(2,3-dibromopropyl) ether (TBBPA-BDBPE) - Yuqing Jiang; Ling Wang; Minggang Zheng; Yongfeng Lin; Aifeng Liu; Yawei Wang; Ying Li (Science of The Total Environment, 2023)

Absence of known knockdown resistance mutations but fixation of CYP337B3 was detected in field populations of Helicoverpa armigera across China - Ruoyao Ni; Yawei Wang; Qiuzan Zhong; Mei Li; Dandan Zhang; Yongjun Zhang; Xinghui Qiu (Pesticide Biochemistry and Physiology, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Identification of natural and anthropogenic sources and the effects of climatic fluctuations and land use changes on dust emissions variations in the Qinghai-Tibetan Plateau - Heqiang Du; Yawei Fan; Lihui Luo; Jie Liao; Zongxing Li; Xiufan Liu; Xinlei Liu; Xian Xue; Tao Wang (Agricultural and Forest Meteorology, 2023)

Impact of pyraclostrobin on the growth of Fusarium pseudograminearum and its control efficacy against wheat crown rot in Henan Province, China - Ying Hou; Yawei Chen; Lili Wang; Yiheng Zheng; Shengming Liu; Jianqiang Xu (Journal of Plant Pathology, 2023)

An extensive assessment of seasonal rainfall on intracellular and extracellular antibiotic resistance genes in Urban River systems - Wenchao Yu; Ye Xu; YaWei Wang; Qianwen Sui; Yuan Xin; Hui Wang; Junya Zhang; Hui Zhong; Yuansong Wei (Journal of Hazardous Materials, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Protective effect of chicken egg yolk immunoglobulin (IgY) against Spiroplasma eriocheiris infection in Chinese mitten crab - Ying Guo; Yubo Ma; Hendriansyah Endri; Yanlan Huang; Xinyu Pan; Suyue Qiu; Yawei Cao; Wei Gu; Jie Du; Li Wang; Qingguo Meng (Aquaculture, 2023)

Experimental research on the flame resistance characteristics of wire mesh for syngas explosion - Xingyan Cao; Zhi Wang; Zhirong Wang; Yawei Lu; Shaochen Sun; Jianjun Xu (Process Safety and Environmental Protection, 2023)

Implementation of solution separation-based Kalman filter integrity monitoring against all-source faults for multi-sensor integrated navigation - Shizhuang Wang; Yawei Zhai; Xingqun Zhan (GPS Solutions, 2023)

Reaction mechanism of NO and SO2 Co-removal by calcium hydroxide - Angran Zhao; Yongqiang Han; Zhipeng Wang; Pengfei Li; Yawei Xu; Ruiming Yang; Huiling Tong (Journal of Environmental Chemical Engineering, 2023)

Distribution characteristics of photoinitiators and their flux estimation from the Pearl River Delta to the coastal waters of the South China Sea - Yuqing He; Zibin Pan; Xinxin Liang; Ruiman Xie; Yuying Sun; Juan Li; Yawei Wang; Lixi Zeng (Journal of Environmental Sciences, 2023)

Efficient anti-frosting on discrete nanoclusters via spatiotemporal control of condensation frosting dynamics - Siyan Yang; Yushan Ying; Wanbo Li; Yawei Feng; Rongfu Wen; Qixun Li; Yuanbo Liu; Bingang Du; Zuankai Wang; Xuehu Ma (Chemical Engineering Journal, 2023)

Pretreatment of moso bamboo with p-toluenesulfonic acid for the recovery and depolymerization of hemicellulose - Meixin Wang; Yawei Zhan; Jiayue Zhao; Zhiqiang Li (Bioresource Technology, 2023)

Mechanism of persistent heavy PM2.5 pollution over the Beijing-Tianjin-Hebei region of China: A combination of aerosol radiative effect and atmospheric quasi-biweekly oscillation - Libo Gao; Tijian Wang; Xuejuan Ren; Danyang Ma; Yawei Qu; Hao Wu (Atmospheric Environment, 2023)

Implementation and analysis of fault grouping for multi-constellation advanced RAIM - Shizhuang Wang; Yawei Zhai; Cheng Chi; Xingqun Zhan; Yiping Jiang (Advances in Space Research, 2023)

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Influence of microplastics on the photodegradation of perfluorooctane sulfonamide (FOSA) - Lingyi Meng; Haoting Tian; Jitao Lv; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Distribution and exposure risk assessment of chlorinated paraffins and novel brominated flame retardants in toys - Ruirui Zhang; Juan Li; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Getting insight into the oxidation of SO2 to SO3 over P modified VW/Ti catalyst: Effect and inhibition mechanism - Zijun Yin; Yuxiu Zhong; Jingwen Lu; Tao Liu; Yawei Song; Mengxia Qing; Lele Wang; Yi Wang; Song Hu; Sheng Su; Jun Xiang (Chemical Engineering Journal, 2023)

From bitter to delicious: properties and uses of microbial aminopeptidases - Yawei Wang; Puying Zhao; Ying Zhou; Xiaomin Hu; Hairong Xiong (World Journal of Microbiology and Biotechnology, 2023)

Environmental characteristics and unified failure mode classification system for mining landslides in the karst mountainous areas of southwestern China - Zuliang Zhong; Yawei Xu; Nanyun Wang; Xinrong Liu; Guofu Gao (Carbonates and Evaporites, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Interfacial role of Ionic liquids in CO2 electrocatalytic Reduction: A mechanistic investigation - Shuai Guo; Yawei Liu; Yanlei Wang; Kun Dong; Xiangping Zhang; Suojiang Zhang (Chemical Engineering Journal, 2023)

Effects of Different Levels of Organic Trace Minerals on Oxidative Status and Intestinal Function in Weanling Piglets - Shangchu Wang; Shujun Wu; Yawei Zhang; Juan Chen; Xihong Zhou (Biological Trace Element Research, 2023)

Potential for selective oxidation of aniline in soil washing effluent by active chlorine and testing its practicality - Yi Ren; Xiangxin Meng; Xuan Zhang; Yuhai He; Guangfei Gao; Pengqi Wang; Yawei Gu; Yue Ding; Wenqiang Jiang (Chemosphere, 2023)

Novel strategies and approaches toward toxicity assessment: a key factor for safety assessment and management of per- and polyfluoroalkyl substances - Yao Lu; Chunyan Zhao; Hanyong Peng; Jinghua Hao; Chunyang Liao; Yong Liang; Yawei Wang; Guibin Jiang (Science Bulletin, 2023)

Evaluating the dynamic distribution process and potential exposure risk of chlorinated paraffins in indoor environments of Beijing, China - Lu Bai; Kun Lv; Juan Li; Wei Gao; Chunyang Liao; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Experimental and theoretical study on the suppression effect of water mist containing dimethyl methylphosphonate (DMMP) on hydrogen jet flame - Zhirong Wang; Hui Xu; Yawei Lu; Zhenhua Tang; Rujia Fan (Fuel, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

MiR-128-3p Attenuates the Neurotoxicity in Rats Induced by Isoflurane Anesthesia - Duo Qian; Shijie Dai; Yujing Sun; Yawei Yuan; Long Wang (Neurotoxicity Research, 2022)

Research on Surrounding Rock Control Technology of Gob-Side Entry Retaining by Directional Roof Cutting in a Deep Coal Mine - Haojie Xue; Shibao Shen; Haoran Lu; Renbao Zhao; Peishuai Li; Yawei Zhao; Qibin Jiang; Longjiang Wang; Beizhan Fan; Tao Qin (Geotechnical and Geological Engineering, 2022)

Magnetic graphene oxide for methylene blue removal: adsorption performance and comparison of regeneration methods - Yawei Shi; Haonan Wang; Guobin Song; Yi Zhang; Liya Tong; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2022)

Water splitting, pollutant degradation and environmental impact using low-index faceted metal-based nanocrystals. A review - Xiang Zhang; Jie Tang; Nali Zhu; Lingxiangyu Li; Yawei Wang (Environmental Chemistry Letters, 2022)

Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.

Variations of human cerebral and ocular blood flow during exposure to multi-axial accelerations - Weipeng Li; Bitian Wang; Yawei Wang; Xiaoyu Liu; Wentao Feng; Tianya Liu; Zhujun Sun; Yu Liu; Songyang Liu; Yubo Fan (Medical & Biological Engineering & Computing, 2022)

A comparative analysis of navigation signals in BDS-2 and BDS-3 using zero-baseline experiments - Chenlong Deng; Shufeng Qi; Yangyang Li; Yawei Wang; Xuan Zou; Weiming Tang; Chi Guo (GPS Solutions, 2021)

Manganese Accumulation and Plant Physiology Behaviour of Camellia oleifera in Response to Different Levels of Phosphate Fertilization - Fangming Yu; Meifen Xin; Yawei Yao; Xueru Wang; Kehui Liu; Yi Li (Journal of Soil Science and Plant Nutrition, 2021)

Visualization of GNSS multipath effects and its potential application in IGS data processing - Weiming Tang; Yawei Wang; Xuan Zou; Yangyang Li; Chenlong Deng; Jianhui Cui (Journal of Geodesy, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Sorptive removal of methylene blue from water by magnetic multi-walled carbon nanotube composites - Guobin Song; Anqi Li; Yawei Shi; Wanran Li; Haonan Wang; Chunchao Wang; Ruijuan Li; Guanghui Ding (Environmental Science and Pollution Research, 2021)

Research on the mechanical properties and electrical conductivity of cement mortar based on recycled nano-iron boride - Wei He; Zhinan Jiao; Yawei Wang; Jihang Xu; Qingxin Zhao (Waste Disposal & Sustainable Energy, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Enterobacter sp. FM-1 inoculation influenced heavy metal-induced oxidative stress in pakchoi (Brassica campestris L. ssp. Chinensis Makino) and water spinach (Ipomoea aquatic F.) cultivated in cadmium and lead co-contaminated soils - Fangming Yu; Yawei Yao; Jingpei Feng; Xueru Wang; Jiangming Ma; Kehui Liu; Yi Li (Plant and Soil, 2021)

Nitrification inhibitor DMPP offsets the increase in N2O emission induced by soil salinity - Yawei Li; Junzeng Xu; Xiaoyin Liu; Zhiming Qi; Haiyu Wang; Youjia Li; Linxian Liao (Biology and Fertility of Soils, 2020)

Neurobehavioral performance of PAH exposure in male coal miners in Shanxi, China: a cross-sectional study - Fang Wang; Liuye Yang; Bin Zhang; Gaisheng Liu; Chongjian Wang; Yawei Zhang; Tong Wang (International Archives of Occupational and Environmental Health, 2020)

Multiplex genome editing using a dCas9-cytidine deaminase fusion in Streptomyces - Yawei Zhao; Jinzhong Tian; Guosong Zheng; Jun Chen; Chuanwen Sun; Zhongyi Yang; Andrei A. Zimin; Weihong Jiang; Zixin Deng; Zhijun Wang; Yinhua Lu (Science China Life Sciences, 2020)

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Lithology identification and reservoir characteristics of the mixed siliciclastic-carbonate rocks of the lower third member of the Shahejie formation in the south of the Laizhouwan Sag, Bohai Bay Basin, China - Yajun Duan; Jun Xie; Baichuan Li; Mengqi Wang; Tianqi Zhang; Yawei Zhou (Carbonates and Evaporites, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

The Influence of Temperature and High-Speed Heating on Tensile Strength of Granite and the Application of Digital Image Correlation on Tensile Failure Processes - Fei Wang; Heinz Konietzky; Thomas Frühwirt; Yawei Li; Yajie Dai (Rock Mechanics and Rock Engineering, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

Losartan suppresses the inflammatory response in collagen-induced arthritis by inhibiting the MAPK and NF-κB pathways in B and T cells - Xinming Wang; Xiaoyun Chen; Wei Huang; Pengying Zhang; Yawei Guo; Heinrich Körner; Huaxun Wu; Wei Wei (Inflammopharmacology, 2019)

A comparison of two methods for estimating surface soil moisture based on the triangle model using optical/thermal infrared remote sensing over the source area of the Yellow River - Long Xia; Xiaoning Song; Pei Leng; Yawei Wang; Yanbin Hao; Yanfen Wang (International Journal of Remote Sensing, 2019)

Ammonia volatilization and nitrogen leaching following top-dressing of urea from water-saving irrigated rice field: impact of two-split surge irrigation - Junzeng Xu; Boyi Liu; Haiyu Wang; Wenhao Liu; Yawei Li; Yubin Dai; Tao Lu (Paddy and Water Environment, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Influence of Atmospheric Particulate Matter on Ozone in Nanjing, China: Observational Study and Mechanistic Analysis - Yawei Qu; Tijian Wang; Yanfeng Cai; Shekou Wang; Pulong Chen; Shu Li; Mengmeng Li; Cheng Yuan; Jing Wang; Shaocai Xu (Advances in Atmospheric Sciences, 2018)

Design of gas drainage modes based on gas emission rate in a gob: a simulation study - Xiaowei Li; Chaojie Wang; Yujia Chen; Jun Tang; Yawei Li (Arabian Journal of Geosciences, 2018)

Three-dimensional distributed DC/IP method for altered tectonite-type gold ore deposits exploration: a case study of the Jiaojia gold metallogenic belt, Eastern China - Jiayong Yan; Yawei Zhang; Kun Zhang; Yongqian Zhang; Hao Hu; Zhihui Wang (Acta Geophysica, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Instantaneous BDS + GPS undifferenced NRTK positioning with dynamic atmospheric constraints - Xuan Zou; Yawei Wang; Chenlong Deng; Weiming Tang; Zongnan Li; Jianhui Cui; Chen Wang; Chuang Shi (GPS Solutions, 2018)

Transcriptome profiles reveal cold acclimation and freezing tolerance of susceptible and tolerant hulless barley genotypes - Hongjun Yuan; Xingquan Zeng; Zhihao Ling; Zexiu Wei; Yulin Wang; Zhenhua Zhuang; Qijun Xu; Yawei Tang; Nyima Tashi (Acta Physiologiae Plantarum, 2017)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.

Erratum to: Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Spatio-temporal distribution of fecal indicators in three rivers of the Haihe River Basin, China - Yawei Wang; Yanan Chen; Xiang Zheng; Chengmin Gui; Yuansong Wei (Environmental Science and Pollution Research, 2017)

Fouling analysis of membrane bioreactor treating antibiotic production wastewater at different hydraulic retention times - Dawei Yu; Yutao Chen; Yuansong Wei; Jianxing Wang; Yawei Wang; Kun Li (Environmental Science and Pollution Research, 2017)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Mapping the effect of escitalopram treatment on amplitude of low-frequency fluctuations in patients with depression: a resting-state fMRI study - Li Wang; Xueni Li; Ke Li; Yunai Su; Yawei Zeng; Qinge Zhang; Gang Wang; Zhen Jin; Qingmei Kong; Tianmei Si (Metabolic Brain Disease, 2017)

Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Hyperthermostable Thermotoga maritima xylanase XYN10B shows high activity at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids - Tianyi Yu; Sasikala Anbarasan; Yawei Wang; Kübra Telli; Aşkın Sevinç Aslan; Zhengding Su; Yin Zhou; Li Zhang; Piia Iivonen; Sami Havukainen; Tero Mentunen; Michael Hummel; et al. (Extremophiles, 2016)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Dynamical analysis of periodic bursting in piece-wise linear planar neuron model - Ying Ji; Xiaofang Zhang; Minjie Liang; Tingting Hua; Yawei Wang (Cognitive Neurodynamics, 2015)

Effects of vegetation and soil texture on surface soil moisture retrieval using multi-temporal optical and thermal infrared observations - Pei Leng; Xiaoning Song; Zhao-Liang Li; Yawei Wang; Di Wang (International Journal of Remote Sensing, 2015)

Uncertainty analysis of SPI calculation and drought assessment based on the application of Bootstrap - Yi‐Ming Hu; Zhong‐Min Liang; Yong‐Wei Liu; Jun Wang; Lei Yao; Yawei Ning (International Journal of Climatology, 2015)
The Standardized Precipitation Index ( SPI ) has been widely used to monitor the drought status. In the estimation of SPI , an appropriate probability distribution function ( APDF ) is required to fit precipitation series with different timescales, such as 3‐month, 9‐month and so on. Then the standard normal distribution function is used to transform the cumulative probability derived from APDF to calculate the SPI value. Obviously, the estimation accuracy of SPI particularly depends on the sample that influences the selection of PDF and parameter estimation. However, the size of the observed sample is usually small, and it cannot perfectly present the statistical property of the population, which usually causes the uncertainty on calculation of SPI and in turn results in the uncertainty of drought assessment. Due to the existence of gap between the estimated SPI and the true SPI , when one obtains the estimation of SPI , it is necessary to know the reliability or uncertainty of the estimated SPI . In this article, a new method based on the Bootstrap method was put forward to analyse the impact of sampling uncertainty on the estimation of SPI and drought assessment. Through repeating samples from the original sample, a large number of Bootstrap samples are constructed, and based on each Bootstrap sample, the corresponding estimation of SPI for the given event can be obtained. Therefore, the sampling distribution of SPI for the given event can also be derived, on which both the point estimation and interval estimation of SPI for the given precipitation event can be provided, and the overall assessment of a drought event could be achieved. The case study shows that, compared with the original SPI calculation method, the proposed method not only provides equivalent assessment results, but also has the capability to assess the impact of sampling uncertainty on the uncertainty of SPI calculation and drought assessment.

Concentrations and Seasonal Variation of Ambient PM2.5 and Associated Metals at a Typical Residential Area in Beijing, China - Jing Yang; Qiang Fu; Xiaoshuang Guo; Baolin Chu; Yawei Yao; Yanguo Teng; Yeyao Wang (Bulletin of Environmental Contamination and Toxicology, 2015)

Air Quality in Lanzhou, a Major Industrial City in China: Characteristics of Air Pollution and Review of Existing Evidence from Air Pollution and Health Studies - Yaqun Zhang; Min Li; Mercedes A. Bravo; Lan Jin; Amruta Nori-Sarma; Yanwen Xu; Donghong Guan; Chengyuan Wang; Mingxia Chen; Xiao Wang; Wei Tao; Weitao Qiu; et al. (Water, Air, & Soil Pollution, 2014)

Land use effects on soil organic carbon, microbial biomass and microbial activity in Changbai Mountains of Northeast China - Xiangmin Fang; Qingli Wang; Wangming Zhou; Wei Zhao; Yawei Wei; Lijun Niu; Limin Dai (Chinese Geographical Science, 2014)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)

Genotype frequency and F ST analysis of polymorphisms in immunoregulatory genes in Chinese and Caucasian populations - Qing Lan; Min Shen; Dino Garcia-Rossi; Stephen Chanock; Tongzhang Zheng; Sonja I. Berndt; Vinita Puri; Guilan Li; Xingzhou He; Robert Welch; Shelia H. Zahm; Luoping Zhang; et al. (Immunogenetics, 2007)

Family history of hematopoietic and non-hematopoietic malignancies and risk of non-Hodgkin lymphoma - Yawei Zhang; Rong Wang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Yong Zhu; Qin Qin; Tongzhang Zheng (Cancer Causes & Control, 2007)

Genetic polymorphisms in the oxidative stress pathway and susceptibility to non-Hodgkin lymphoma - Qing Lan; Tongzhang Zheng; Min Shen; Yawei Zhang; Sophia S. Wang; Shelia H. Zahm; Theodore R. Holford; Brian Leaderer; Peter Boyle; Stephen Chanock (Human Genetics, 2007)

Polymorphisms in DNA repair genes and risk of non-Hodgkin lymphoma among women in Connecticut - Min Shen; Tongzhang Zheng; Qing Lan; Yawei Zhang; Shelia H. Zahm; Sophia S. Wang; Theodore R. Holford; Brian Leaderer; Meredith Yeager; Robert Welch; Daehee Kang; Peter Boyle; et al. (Human Genetics, 2006)